THE HIGH PERFORMANCE WORK EVIRONMENT AND EMPLOYEE ENGAGEMENT ON MILLENIALS GENERATION WORKING AT GREEN BUSINESS ORGANIZATION - Alvina Putri Prasetyanto; Noviaty Kresna Darmawan; J. L. Eko Nugroho (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
This research analyzes the influence of high performance work environment and employee engagement on millennials working in companies that implement green business. The type of research used mixed methods, i.e. quantitative methods that are equipped with qualitative methods. Variables tested are based on the dimensions expressed. Taking data using questionnaires, the study respondents were millennials working in the green business organization.The purpose of this study is to look at the influence of high performance work environment factors on employee engagement in millennials working in companies that implement green business.The results showed that there is a significant influence between high performance work factors on employee engagement in millennials working in green business organizations. Keywords: high performance work environment, employee engagement, green business organization.